Chapter: 'User Motivation and Technology Acceptance in Online Learning Environments' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Maxime Pedrotti (Lecture Notes in Computer Science, 2016)
Research on technology acceptance in educational contexts often shows little or no influence of user acceptance on use intention or use behavior. While recent attempts to factor in learners' motivation appear promising, the problem of limited explanatory value of technology acceptance models remains. This paper further explores the relationship between motivational and acceptance factors in different learning contexts. Data (N = 673) from four studies conducted among users of two online learning environments at a major university in Germany are analyzed using a combined data set containing items relating to user motivation (according to Self-Determination Theory) and technology acceptance (according to the Unified Theory of Acceptance and Use of Technology). The data show significant differences in acceptance and motivational levels between these four groups, as well as a connection between acceptance and motivation. Implications of these results include a recommendation to revisit UTAUT assumptions and variables in future research.